677 PREDICTION OF RIGHT VENTRICULAR FAILURE AFTER LEFT VENTRICULAR ASSIST DEVICE IMPLANTATION: ROLE OF VASODILATOR CHALLENGE. (15th December 2022) - Cacioli, Giulio; Polizzi, Vincenzo; Ciabatti, Michele; Cristiano, Ernesto; Pergolini, Amedeo; Distefano, Giada; Della Monica, Paola Lilla; Comisso, Marina; Piazza, Vito; Sbaraglia, Fabio; Musumeci, Francesco
Abstract: Pulmonary artery pulsatility index (PAPi) is an indicator of right ventricular (RV) function and an independent predictor of right ventricular failure (RVF) following left ventricular assist device (LVAD) implantation. Administration of vasodilator challenge during right heart catheterization (RHC) could reduce RV workload allowing a better assessment of its functional reserve. Patients undergoing LVAD implantation at our Institution between May 2013 and August 2021 were enrolled. Only patients who had undergone RHC and vasodilator challenge with sodium nitroprusside were analyzed. We collected all available clinical, instrumental, and haemodynamic parameters, at baseline and after nitroprusside infusion and evaluated potential associations with post-LVAD RVF. Of the 54 patients analyzed, 19 (35%) developed RVF after LVAD implantation. Fractional area change (FAC) (OR: 0.647, CI: 0.481–0.871; P = 0.004), pulmonary artery systolic pressure (PASP)(OR: 0.856, CI: 0.761–0.964; P=0.010), and post-sodium nitroprusside (NTP) PAPi (OR: 0.218, CI: 0.073–0.653; P = 0.006) were independent predictors of post-LVAD RVF. The model combining FAC, PASP, and post-NTP PAPi demonstrated a predictive accuracy of 90.7%. Addition of post-NTP PAPi significantly increased the predictive accuracy of the European Registry for Patients with Mechanical Circulatory Support right-sided heart failure risk score [79.4 vs. 70.4%; area under the curve (AUC): 0.841 vs. 0.724, P = 0.022] and the CRITT score (79.6% vs. 74%; AUC: 0.861 vs. 0.767 P = 0.033). Post-NTP PAPi has observed to be an independent predictor of RVF following LVAD implantation. Dynamic assessment of PAPi using a vasodilator challenge may represent a method of testing RV functional reserve in candidates for LVAD implantation. Larger and prospective studies are needed to confirm this hypothesis.